Влияние Фармакологических Препаратов А Гистоструктуру И Содержание Гликогена В Печени - Низом, Фармонов; ўғли, Омонов Шоҳзод Кахрамон; ўғли, Рахмадуллаев Ҳумоюн Рашид (Journal of Science in Medicine and Life, 2023)
The Russian language is used as a means of interethnic communication in the near abroad. Currently, Russian is one of the languages of European and World importance. Along with English, French, Spanish, Chinese, and Arabic, it is recognized as the official and working language of the United Nations. Modern Russian literary language is studied by more than 250 million people in about 100 countries of the world.